Unexpected hormonal and behavioral responses to anthropogenic stressors in young common toads - Ujhegyi, Nikolett; Bombay, Bálint; Gabor, Caitlin R.; Bókony, Veronika (Frontiers in Amphibian and Reptile Science, 2025)
IntroductionAnthropogenic conversion of natural habitats is one of the most significant threats to biodiversity, and it is also partially responsible for the largest recorded decline in amphibians. Urbanization exposes wildlife to increased disturbance by proximity to humans, artificial light at night (ALAN), and noise pollution, all of which can be harmful to wild animals. Glucocorticoid hormones may play an important role in coping with environmental challenges. A growing body of evidence indicates in various vertebrate species that more efficient regulation of the glucocorticoid stress response may be favored by natural selection under stressful environmental conditions. In several species, baseline levels of glucocorticoids and also their response to acute stressors are repeatable, heritable, and related to individual fitness. However, in these latter respects, our knowledge is scarce for other aspects of glucocorticoid flexibility, such as the ability to recover from acute stress by negative feedback.MethodsTo address this knowledge gap, we measured the repeatability of four aspects of the corticosterone (CORT) profile (baseline release rate, strength of stress response to agitation, rate of recovery by negative feedback, and a recently proposed measure of sequential variability) over the ontogeny of tadpoles and juveniles of the common toad (Bufo bufo). Thereafter we measured the toadlets’ behavioral responses to three anthropogenic stressors, specifically their hop performance while fleeing from a human, and foraging rate under ALAN and during daytime noise pollution, to test whether the hormonal characteristics explain the behavioral differences between individuals.ResultsWe found that the CORT profile changed during ontogeny, and all its measured aspects had low repeatability. Foraging rate increased in response to both ALAN and noise, and the two responses were correlated within individuals, but not with fleeing performance. None of the behavioral variables correlated with the CORT variables.DiscussionOur results suggest that this widespread species, found in anthropogenic environments, has limited individual consistency in tolerance to anthropogenic stressors during early development, pointing to the importance of phenotypic plasticity in coping with the challenges of urban environments.